Rapport and Knowledge: Enhancing Foreign Instructor Credibility in the Classroom. (June 2014) - Zhang, Mei
Abstract : This chapter discusses strategies to establish rapport and demonstrate knowledge in order to enhance instructor credibility and create a productive learning environment in the oral performance class.